PENGARUH PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Devi Silvia Simanjuntak; Paul Eduard Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
During the last 5 years, the occurrence of depreciation in the value of the company exceeded 50% of the total industry in the property and real estate sub- sector. Therefore, this study aims to examine the effect of tax planning on firm value. The sampling technique used purposive sampling and obtained 17 property and real estate sub-sector companies listed on the Stock Exchange with the observation year 2016-2020 so that the number of observations was 85. Based on the results of data processing using simple linear regression analysis, it was found that there was no effect of tax planning on firm value of property and real estate 2016-2020. Thus, it is recommended for further researchers to add independent variables such as deferred tax burden.